Análise da gestão integrada de agroecossistemas no Haiti: caso de Haut-Limbé - Saint-Fleur, Weldy (2021)
In this work we analyze the integrated management of agroecosystems in Haiti, particularly in the 3rd section of Haut-Limbé by farmers on ecological, social, economic, and cultural levels. This region is characterized by a traditional agriculture and by a plurality of agricultural crops and typical products. It covers approximately 23.95 km2 with predominantly mountainous terrain and has its own agricultural, social, and cultural characteristics. The essay is divided into two chapters. The first deals with the dynamics of land use change in Haut-Limbé between 2016 and 2021, determined by satellite imagery and spatialization of the data in a geographic information system (GIS). The results showed that during this period the changes were more important in the classes of degraded soil, pasture/crop and dense vegetation. The second chapter deals with the management of agroecosystems by farmers in Haut-Limbé, based on information collected during semi-structured interviews with 30 heads of family farms. The cartographic tool for spatially representing the agricultural plots of the group concerned was also used. In view of the above, farmers in Haut-Limbé interact with their landscape to ensure their survival and shape their society. However, the trend shows that this same landscape is in decline, marked by the reduction of vegetation cover and soil degradation. We assume that the trend will be exacerbated by 2030. The situation must be taken seriously as a matter of urgency to avoid the collapse of the Haut-Limbé community.